2011
DOI: 10.1007/s00234-011-0844-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of DTI in early detection of cervical spondylotic myelopathy: a preliminary study with 3-T MRI

Abstract: Our preliminary findings indicate that DTI may show abnormalities in the spinal cord before the development of T2 hyperintensity on conventional sequences in patients with CSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 24 publications
11
66
1
4
Order By: Relevance
“…The FA value of healthy cord found in our study was 0.65±0.07 (C2-C7), which is in agreement with earlier reports: from 0.74±0.01 (C2) to 0.56±0.02 (C7), 4 0.721±0.027 (C2-C7), 38 0.57±0.04 (C2-C7), 39 and 0.61±0.05. 40 The FA value measured in myelopathic cord was 0.53±0.10, which was also comparable with 0.311-0.621 41 and 0.498±0.114. 42 Notably, the FA value measured in this study is slice averaged rather than being measured at compression level or stenotic segments, due to the following reasons: 1) FA value in the spinal cord is decreased with level, 38,39 thus the values at different levels should be normalized before comparison.…”
Section: Methodological Considerations and Spinal Bold Response Relatsupporting
confidence: 72%
“…The FA value of healthy cord found in our study was 0.65±0.07 (C2-C7), which is in agreement with earlier reports: from 0.74±0.01 (C2) to 0.56±0.02 (C7), 4 0.721±0.027 (C2-C7), 38 0.57±0.04 (C2-C7), 39 and 0.61±0.05. 40 The FA value measured in myelopathic cord was 0.53±0.10, which was also comparable with 0.311-0.621 41 and 0.498±0.114. 42 Notably, the FA value measured in this study is slice averaged rather than being measured at compression level or stenotic segments, due to the following reasons: 1) FA value in the spinal cord is decreased with level, 38,39 thus the values at different levels should be normalized before comparison.…”
Section: Methodological Considerations and Spinal Bold Response Relatsupporting
confidence: 72%
“…Cerebrospinal fluid flow disturbances, resulting from degenerative changes both in static position and during movement, could increase the pressure around the spinal cord and, in turn, alter interstitial diffusion which would result in DTI metrics changes [6]. The differences in FA and ADC values between control group and groups representing advanced, degenerative changes (D, E) were obvious, and has been already described by many authors [1,[6][7][8][13][14][15].…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, DTI seems to be sensitive to pathological processes altering water diffusion at a microscopic level, far beyond the resolution of conventional MR imaging [13]. Several investigators have carried out DTI studies in patients suffering from CSM [1,[6][7][8][13][14][15]. They found significant differences in FA and ADC values between patients and normal volunteers, even in the absence of T2 hyperintensity of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) improves pathologic specificity by measuring directional diffusivities, which quantify water diffusion parallel and perpendicular to the white matter tracts [16,29] . A recent study of the role of DTI in cervical spondylotic myelopathy suggested that DTI may elucidate pathology of the spinal cord before the development of T2 hyperintensity imaging and thus may be a superior imaging modality in the future [13] . Ectopic ossification of spinal ligaments: Ectopic ossification and calcification of spinal ligaments has also been attributed to the development of spinal canal stenosis and the onset and aggravation of myelopathic symptoms [1,30] .…”
Section: Static Mechanical Factorsmentioning
confidence: 99%
“…Whilst the aetiology of cervical myelopathy is thought to be multifactorial including contributions from age-related degeneration, mechanical stress and biochemical factors, a genetic predisposition has been revisited, due to recent evidence of familial clustering in population studies [12] . Despite advances in the surgical management of cervical myelopathy in addition to earlier diagnosis facilitated by advances in diffusion tensor magnetic resonance imaging (MRI) and kinetic MRI, a significant proportion of patients suffer residual neurological sequele as a consequence of irreversible cord injury [13][14][15][16][17] . Thus, implementation of neuro-protective interventions as an adjunct to surgical decompression may optimise patient outcomes for cervical myelopathy.…”
Section: Introductionmentioning
confidence: 99%